Pengaruh Debt Default, Opinion Shopping, dan Kepemilikan Manajerial Terhadap Opini Audit Going Concern: Studi Empiris Pada Perusahaan Sektor Transportasi dan Logistik di Bursa Efek Indonesia Tahun 2017-2021 - Maulana, Ilham; Utami, Tri (Institut Bisnis dan Informatika Kesatuan, 2023)
This study aims to empirically prove the effect of default debt, opinion shopping, and managerial ownership on going concern audit opinions. The independent variables used in this study are Debt default, Opinion shopping, and Managerial Ownership while the dependent variable is Going concern Audit Opinion. This research was conducted at Transportation Sector companies Listed on the Indonesia Stock Exchange in 2017-2021. The research method used is a quantitative method. The type of data used is secondary data in the form of annual published reports of companies listed on the Indonesia Stock Exchange (IDX) for 2017-2021. Samples were collected by purposive sampling method. Data processing uses Eviews version 12 by collecting related data. The number of samples studied is 50 observational data from 10 sample companies. The results of this study indicate that debt default, opinion shopping and managerial ownership have a simultaneous effect on going concern audit opinions. Variable debt default and opinion shopping partially have no effect on going-concern audit opinion, while managerial ownership partially has a significant effect on going-concern audit opinion